Successful percutaneous revascularization in a left lower limb with below-the-knee amputation - (:unkn) unknown (My University, 2022)
79 year-old male patient with diabetes mellitus, hypertension and left sided below-the-knee amputation history was admitted to our clinic, complaining inability to use his prosthetic leg because of unhealed wounds in amputation site. Physical examination showed no pulse on the left femoral artery. Arterial Doppler ultrasonography revealed monophasic flow in the left superficial femoral artery (SFA). Peripheral angiography was performed and it demonstrated critical stenosis in the proximal SFA, and in the deep femoral artery (DFA) and total occlusion in the distal SFA without distal collateral filling. Percutaneous intervention was planned. We accessed through right femoral artery with 6F sheath, and 6F sheathless catheter was advanced to the left common femoral artery by crossover technique. Critical stenosis and occlusion in the left SFA were crossed using 0.035 hydrophilic wire and 5.0x100 mm balloon for support. Distal true lumen was confirmed by contrast guided imaging. Repeated dilations were performed with 5.0x100 mm and 4.0x20 mm balloons. After that, lesions in the DFA were crossed using 0.014 hydrophilic wire (Pilot 150) and they were also dilated with 4.0x20 mm balloon. Control angiogram demonstrated sufficient flow in the SFA and DFA without flow limiting dissection, reaching to the amputation level. His wounds healed within 3 weeks and one month after this procedure he was be able to use his prosthetic leg.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); amputation; balloon; catheter